TINJAUAN YURIDIS TINDAK PIDANA KORUPSI SEBAGAI EXTRA ORDINARY CRIME - ROY GANDA MARBUN; IDA LAMSIHAR SITOMPUL; MIDARMI HALAWA; INDAH PRIHATIANI MALAU PASA; GANESHA PUTRA PURBA (LP2MTBM MAKARIOZ, 2020)
The Extra Ordinary Crimes criminal offence qualification needs to be arranged into special criminal law because it isspecifically regulated in some laws in Indonesia, because in the practice of the national legal mechanism is not able toprovide a fair settlement against the extraordinary crimes therefore legislation outside the book of Criminal Law whichgoverns the crimes that enter into qualification as an extraordinary crime. The evils of today are no longer always using theold ways that have occurred over the years as the journey of the Earth ages. Of the many types of crimes that occur inpeople's lives, there is a type of crime that affects the safety and peace of the world, i.e. extra ordinary crime or better knownas extraordinary crime term. When viewed from its history, extraordinary crimes only include 4 types of crimes namely warcrimes, crime of aggression, crime of genocide and crimes against humanity. However, the development of evil now showsthat there are some recent crimes assumed to be equal to the four types of crimes. Terrorism crimes are often interpreted asextraordinary crimes because of the effects of evil it is almost the same as the four types of crimes.